2020
DOI: 10.1177/0284185120958407
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of iliotibial band diameter in iliotibial band friction syndrome and comparison with an asymptomatic population

Abstract: Background Iliotibial band friction syndrome (ITBFS) is an overuse injury of the lateral aspect of the knee. This syndrome classically affects the active young population. Purpose To determine the diameter of the ITB using magnetic resonance imaging (MRI) in patients clinically diagnosed with ITBFS, compare the results with asymptomatic patients, and assess the inter-observer agreement between a senior and a junior radiologist with different levels of experience in musculoskeletal imaging. Material and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…In this study, lateral epicondyle prominence, thick ITB-d, and larger ITB-a were found to be significantly associated factors with ITBFS. This is in line with the results of the previous studies reporting that patients with ITBFS had higher ITB thickness, ITB-a, and lateral epicondyle height than those without ITBFS [ 6 , 8 , 9 ]. There was still controversy as to whether the thick ITB caused symptoms or the misuse injury caused the ITB-d to increase [ 8 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, lateral epicondyle prominence, thick ITB-d, and larger ITB-a were found to be significantly associated factors with ITBFS. This is in line with the results of the previous studies reporting that patients with ITBFS had higher ITB thickness, ITB-a, and lateral epicondyle height than those without ITBFS [ 6 , 8 , 9 ]. There was still controversy as to whether the thick ITB caused symptoms or the misuse injury caused the ITB-d to increase [ 8 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, accurate diagnosis of ITBFS is important. Previous studies reported that a higher position of patella (patella alta), lateral epicondyle prominence (increment in lateral epicondyle height), thick ITB, and larger ITB-a were the morphological features associated with ITBFS [ 6 9 ]. However, these are subjectively measured values and there are not many studies on their reliability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In addition to this, risk factors such as weakness in hip abductors, gait abnormalities, and increased ITB thickness have been established in further studies. 14 15 16…”
Section: Iliotibial Band Friction Syndromementioning
confidence: 99%